A) 3(x-2)-4(2x+5)=13x+10
b) 2x-13=5-(3x-7)
c) 2=-(-2x+6)+2(4x-11)
d) x+1=-2(x+3)-3(x-2)+3
e)-3(2x-5)+(7x-9)=-5x-2(9-3x)+24
f)5x-7(-2-5x)=13(1-2x)-113
Ajuta-ti-ma va rog frumos ! Am nevoie ! Multumesc mult

1

Răspunsuri

2014-05-28T09:34:10+03:00
a) 3(x-2)-4(2x+5)=13x+10
3x-6-8x-20=13x+10 ⇒ -5x-13x= 36⇒ x= -2
b) 2x-13=5-(3x-7)
2x+3x=13+5+7 ⇒ 5x=25⇒ x=5
c) 2=-(-2x+6)+2(4x-11)
2= 2x-6 +8x-22 ⇒30=10x ⇒x=3
d) x+1=-2(x+3)-3(x-2)+3
x+2x+3x= -1-6+6+3 ⇒6x=2 ⇒x= 1/3
e)-3(2x-5)+(7x-9)=-5x-2(9-3x)+24
-6x + 15 + 7x -9 = -5x -18 +6x +24 ⇒ x +5x - 6x =6 -6 ⇒0= 0 , x poate lua orice valoare
f)5x-7(-2-5x)=13(1-2x)-113

5x +14+35x = 13-26x -113
66x = -114⇒ 33x = - 57 ⇒ x= - 57/33